Description of the V instar nymph of Tolono confusus Carvajal, Rider and Faúndez, 2015 (Hemiptera: Heteroptera: Acanthosomatidae) - Carvajal, Mariom A.; Faúndez, Eduardo I.; Rider, David A. (My University, 2022)
Abstract The fifth instar nymph of Tolono confusus Carvajal, Rider & Faúndez, 2015 is described and illustrated based on two specimens from Napo Province, Ecuador. The need for further work on South American pentatomoid immatures stages is briefly discussed.
Keywords: ditomotarsinae; immature stages; pentatomoidea; tolono